2017
DOI: 10.7150/ijms.17585
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Decreased Renal Function after Hand-Assisted Laparoscopic Donor Nephrectomy: A Multivariate Analysis of a Single Surgeon Experience

Abstract: Background: Hand-assisted laparoscopic donor nephrectomy is a minimally invasive procedure for living kidney donation. The surgeon operative volume is associated with postoperative morbidity and mortality. We evaluated the risk factors associated with decreased renal function after hand-assisted laparoscopic donor nephrectomy performed by a single experienced surgeon.Methods: We included living renal donors who underwent hand-assisted laparoscopic donor nephrectomy by a single experienced surgeon between 2006 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Part of that workup includes an analysis of the patient's BMI. There have been conflicting studies regarding the association between donor BMI and postoperative renal compromise [1][2][3][4][5][6][7][8]. Motivated by these conflicting studies, we examine the association of kidney MAP score with postoperative renal function in healthy donors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of that workup includes an analysis of the patient's BMI. There have been conflicting studies regarding the association between donor BMI and postoperative renal compromise [1][2][3][4][5][6][7][8]. Motivated by these conflicting studies, we examine the association of kidney MAP score with postoperative renal function in healthy donors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have evaluated the impact of various preoperative patient-specific and imaging-derived characteristics on postoperative renal function following donor nephrectomy. Examinations of large cohorts of patients suggest that age, male sex, and body mass index (BMI) are predictive of decreased postoperative renal function in patients undergoing donor nephrectomy [1][2][3][4]. However, other studies have shown that BMI has no effect on long term glomerular filtration rate (eGFR) in the donor nephrectomy population [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Men are reported to show a significant decline in the GFR and effective renal plasma flow between the ages of 20 and 50 years; this result is not seen in women, who are probably protected by estrogens in the premenopausal period [ 23 ]. Some studies have indicated that male sex is risk factor of decreased renal function after donor nephrectomy [ 24 25 26 27 ], Lim et al [ 26 ] pointed out sex hormones are involved in the reduction of kidney function after donor nephrectomy in their study. Ibrahim et al [ 20 ] reported that, through long-term follow-up after kidney donation, albuminuria was less likely to develop in females.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure was defined as an ejection fraction of < 40%. The GFR was calculated using the Chronic Kidney Disease Epidemiology Collaboration equation [21,22].…”
Section: Data Collectionmentioning
confidence: 99%